Ecology of aquatic worms in the Langat River, Selangor Peninsular Malaysia. - Abd Aziz, Nor Azwady; Yan, Yi Wei; Mustafa, Muskhazli; Arshad, Aziz (INSInet Publication, 2010)
A study was conducted to determine the diversity and density of aquatic worms in Langat River, Selangor, Peninsular Malaysia and its relationship with the physicochemical parameters that influence the distribution of the worms. The three annelid species found were the oligochaetes, Limnodrilus sp. and Dero sp. and the polychaetes from family Nereididae. The density of different taxonomic groups differed among the sites with all the aquatic worms showing correlation with the physicochemical parameters studied (except conductivity). Dero sp., Limnodrilus sp. and Nereididae showed negative correlation with dissolved oxygen. The aquatic worms showed positive correlation with temperature and organic matter content. Dero sp. (r=0.135) showed positive correlation with pH but both Limnodrilus sp. (r=-0.727) and Nereididae (r=-0.420) showed a negative correlation.